2013
DOI: 10.1503/cjs.22712
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcomes and cost estimation for extra-articular and simple intra-articular distal radius fractures treated with open reduction and internal fixation versus closed reduction and percutaneous Kirschner wire fixation

Abstract: Background:We sought to compare direct costs and clinical and radiographic outcomes for distal radius fractures (DRF) treated with open reduction internal fixation with volar locking plates (VLP) versus closed reduction and percutaneous pinning (CRPP). Methods:We identified patients with AO-type A and C1 DRFs from a prospective database. Outcomes were assessed at 6 weeks and at 3, 6 and 12 months, and surgical care costs were estimated.Results: Twenty patients were treated with CRPP and 24 with VLP. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 9 publications
0
32
0
1
Order By: Relevance
“…It has been argued that in the absence of convincing evidence of superiority of volar locking plates, economic considerations should drive clinical decision-making and policy in the treatment of dorsally displaced distal radius fractures [8,9,40]. However, a robust economic analysis will need to consider differences in costs associated with complications (eg, antibiotic treatment for superficial infections) in addition to differences in costs of the implants, length of surgery, requirement for adjunctive treatments (eg, external fixation, casting), and postoperative protocols (eg, clinic visits, radiographs) [8].…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that in the absence of convincing evidence of superiority of volar locking plates, economic considerations should drive clinical decision-making and policy in the treatment of dorsally displaced distal radius fractures [8,9,40]. However, a robust economic analysis will need to consider differences in costs associated with complications (eg, antibiotic treatment for superficial infections) in addition to differences in costs of the implants, length of surgery, requirement for adjunctive treatments (eg, external fixation, casting), and postoperative protocols (eg, clinic visits, radiographs) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Restoration of volar tilt was significantly better in the VLP group at all time-points, but there was no clinically relevant difference between groups beyond 6 mo, revealing that advantages of VLPs may subside over time. Similarly, Dzaja et al 17 reviewed 44 patients from a prospective database and found no difference between VLP and closed reduction, percutaneous pinning (CRPP) in patient-rated wrist evaluation scores at any time point, although VLPs maintained radial height better over time. A randomized controlled trial conducted by Karantana et al 14 compared the outcomes of 130 displaced distal radial fractures treated with either VLP or percutaneous Kirschner-wire and bridging external fixation.…”
Section: Volar Platesmentioning
confidence: 97%
“…13 During the review period (2013--2014), several level 1 investigations involving volar locking plates were published. 17 In contrast to these findings, a level 1 randomized study performed by Williksen et al 18 randomized 111 unstable distal radial fractures to treatment with a VLP or external fixation with adjuvant pins. At 6 wk, the VLP group had superior outcomes in nearly all radiographic and clinical categories.…”
Section: Volar Platesmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have shown that bridging external fixation, non-bridging external fixation, K-wire fixation, plaster fixation, dorsal plating, volar plating and dorsal and volar plating have high efficacy for DRF treatment [12, 17, 19]. However, there have been several attempts to rank the seven treatment strategies, and disagreements exist on their efficacy in treatment of DRF [11, 15, 20]. …”
Section: Introductionmentioning
confidence: 99%